2023
DOI: 10.3389/fimmu.2023.1039244
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells are associated with impaired Th1 and Th17 responses and severe pulmonary paracoccidioidomycosis which is reversed by anti-Gr1 therapy

Abstract: Previous studies on paracoccidioidomycosis (PCM), the most prevalent systemic mycosis in Latin America, revealed that host immunity is tightly regulated by several suppressive mechanisms mediated by tolerogenic plasmacytoid dendritic cells, the enzyme 2,3 indoleamine dioxygenase (IDO-1), and regulatory T-cells (Tregs). IDO-1 orchestrates local and systemic immunosuppressive effects through the recruitment and activation of myeloid-derived suppressor cells (MDSCs), a heterogeneous population of myeloid cells po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 87 publications
(135 reference statements)
1
7
0
Order By: Relevance
“…The Th17 response, although described as a crucial T cell subset in granuloma formation, it has never been described inside a chronic PCM granulomatous lesion ( Tristão et al., 2017 ). However, IL-17 expressing cells were found in the skin and mucosal lesions of patients ( Pagliari et al., 2011 ) besides a protective role of Th17 cells that has been described by our group ( Galdino et al., 2018 ; Preite et al., 2023 ). The depletion of myeloid-derived suppressor cells (MDSCs) as well as Treg cells leads to robust Th1/Th17 lymphocyte responses associated to a regressive disease with reduced fungal burden, lung pathology and mortality ratios in mice ( Galdino et al., 2018 ; Preite et al., 2023 ).…”
Section: Discussionsupporting
confidence: 62%
“…The Th17 response, although described as a crucial T cell subset in granuloma formation, it has never been described inside a chronic PCM granulomatous lesion ( Tristão et al., 2017 ). However, IL-17 expressing cells were found in the skin and mucosal lesions of patients ( Pagliari et al., 2011 ) besides a protective role of Th17 cells that has been described by our group ( Galdino et al., 2018 ; Preite et al., 2023 ). The depletion of myeloid-derived suppressor cells (MDSCs) as well as Treg cells leads to robust Th1/Th17 lymphocyte responses associated to a regressive disease with reduced fungal burden, lung pathology and mortality ratios in mice ( Galdino et al., 2018 ; Preite et al., 2023 ).…”
Section: Discussionsupporting
confidence: 62%
“…Here, we showed that the inhibition of IDO-1 by 1MT in MDSCs co-cultured with lymphocytes resulted in a higher rate of T-cell proliferation compared to untreated MDSCs. These findings suggest that, despite the activity of other immunosuppressive mechanisms in MDSCs during P. brasiliensis infection 17 , IDO-1 contributes to the suppressive activity of MDSCs. Interestingly, IDO-1 expression did not enhance MDSC differentiation or influx towards the lungs of P. brasiliensis -infected mice.…”
Section: Discussionmentioning
confidence: 82%
“…Although few studies have addressed the involvement of MDSCs in fungal infections 15 , 16 , the role of MDSCs in PCM has been recently investigated by our group. Preite et al 17 showed that MDSCs are recruited to the lungs of P. brasiliensis -infected mice and express the immunosuppressive enzyme Indoleamine 2,3 Dioxigenase-1 (IDO-1), which contributes to impaired Th1 and Th17 responses in the disease, resulting in a severe pulmonary PCM that could be reversed by MDSC depletion in mice 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the characteristic immunosuppression observed in PCM patients has been associated with a high number of Treg cells expressing FoxP3 in lesions and blood [ 65 ]. Of note, the severity of PCM in mice is also affected by the action of myeloid-derived suppressor cells, which contribute to the suppressive microenvironment by producing immunosuppressive molecules and disrupting the activation of T lymphocytes [ 66 , 67 ]. Moreover, it has been described that Treg cell depletion in PCM induces a Th1/Th17 response, associated with a regressive disease with a lower fungal burden [ 68 ].…”
Section: Discussionmentioning
confidence: 99%